2022
DOI: 10.1038/s41421-021-00355-1
|View full text |Cite
|
Sign up to set email alerts
|

Truncated PARP1 mediates ADP-ribosylation of RNA polymerase III for apoptosis

Abstract: Caspase-mediated cleavage of PARP1 is a surrogate marker for apoptosis. However, the biological significance of PARP1 cleavage during apoptosis is still unclear. Here, using unbiased protein affinity purification, we show that truncated PARP1 (tPARP1) recognizes the RNA polymerase III (Pol III) complex in the cytosol. tPARP1 mono-ADP-ribosylates RNA Pol III in vitro and mediates ADP-ribosylation of RNA Pol III during poly(dA-dT)-stimulated apoptosis in cells. tPARP1-mediated activation of RNA Pol III facilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 69 publications
0
18
0
Order By: Relevance
“…But PARP1 induces cell death for genome integrity in the case of extensive damage [17]. With the research goes further, PARP1 is reported be involved in many cellular processes such as cell apoptosis [18,23], chromatin remodeling [38] and gene expression [20,39]. PARP1 is also involved in malignant tumors development and resistance of cancers [40][41][42][43][44], and it is regarded as a potential therapeutic target in certain leukemia [24,45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But PARP1 induces cell death for genome integrity in the case of extensive damage [17]. With the research goes further, PARP1 is reported be involved in many cellular processes such as cell apoptosis [18,23], chromatin remodeling [38] and gene expression [20,39]. PARP1 is also involved in malignant tumors development and resistance of cancers [40][41][42][43][44], and it is regarded as a potential therapeutic target in certain leukemia [24,45].…”
Section: Discussionmentioning
confidence: 99%
“…Poly (ADP-ribose) polymerase 1 (PARP1) is the founding member of PARP family [16,17], which participates in DNA repair and gene integrity [18][19][20]. And excessive activation of PARP1 induced by oxidative stress leads to the depletion of ATP, which causes cell apoptosis [21].…”
Section: Introductionmentioning
confidence: 99%
“…In the apoptotic vesicle caspase 9 is activated, with further activation of caspase 3 and 7, leading to apoptosis ( 29 31 ). During apoptosis, caspase 3 cleaves PARP1, and the increase of cleaved PARP1 hinders DNA damage repair and further promotes apoptosis ( 32 ). Normally, p21 binds to CDKs to block CDK protein activity causing cell cycle arrest ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that PARP1 also negatively regulates TMEJ through Polθ PARylation to maintain appropriate activity of the TMEJ pathway. RNA polymerase III is a binding partner of truncated PARP1, and three subunits (POLR3B, POLR3F, and POLR3G) can be ADP-ribosylated during cytosolic DNA-induced apoptosis (Chen et al, 2022). In addition, PARP1 inhibits elongation of RNA polymerase II via suppressing the transcription elongation factor P-TEFb.…”
Section: Enzymes Involved In Nucleic Acid Processingmentioning
confidence: 99%